2015
DOI: 10.1017/jie.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Voice: Aboriginal Parents, Experiences and Perceptions of Sending a Child to Boarding School in Western Australia

Abstract: This study explored the experience of having a child educated away from home at boarding school for Aboriginal parents living in regional and remote communities in Western Australia (WA). In-depth interviews were conducted with 11 participants and thematic analysis found the following major themes emerged from the data: (1) Access, Standards and Quality, and the subthemes of Declining Local Schools, Opportunity, and Worldliness; (2) Parental Agency and the subthemes of Parent-School Connection, Parenting Style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…The decision to send children for long periods of time to a school away from traditional homelands and often without strong awareness of Aboriginal or Torres Strait Islander culture requires a firm belief in the utility of such education (Bobongie, 2017;Mander, 2015 The first sub-theme that emerged as a benefit of and reason for choosing to attend boarding school, was access to improved education and career pathways, a finding that was consistent with other recent research (Mander, 2015;O'Bryan, 2016). Within this broad goal, students fell into two categories: those who intended to enter employment or vocational training upon completion of secondary school, and those who planned to go on to tertiary education.…”
Section: Educational Utility Of Boardingsupporting
confidence: 65%
See 2 more Smart Citations
“…The decision to send children for long periods of time to a school away from traditional homelands and often without strong awareness of Aboriginal or Torres Strait Islander culture requires a firm belief in the utility of such education (Bobongie, 2017;Mander, 2015 The first sub-theme that emerged as a benefit of and reason for choosing to attend boarding school, was access to improved education and career pathways, a finding that was consistent with other recent research (Mander, 2015;O'Bryan, 2016). Within this broad goal, students fell into two categories: those who intended to enter employment or vocational training upon completion of secondary school, and those who planned to go on to tertiary education.…”
Section: Educational Utility Of Boardingsupporting
confidence: 65%
“…What is known about the experiences and beliefs of boarding school staff, and Indigenous parents and families? In recent years, important ethnographic work has been published on the experiences of Aboriginal and Torres Strait Islander students and perceptions of families and staff regarding boarding school (Bobongie, 2017;Guenther et al, 2016;Mander, 2015;Mander, Cohen, & Pooley, 2015aO'Bryan, 2016). On the one hand, Bobongie's research with Torres Strait Islander girls in three boarding schools in Eastern Australia (2017), Mander's work with Aboriginal boys in five Perth boarding schools and O'Bryan's work with Aboriginal and Torres Strait Islander boarding alumni, have highlighted the motivations which drive Indigenous families to seek out boarding school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Mander (2015 p.184) revealed that education was perceived by Indigenous parents as a means of meeting the expectations of past generations. They wanted their children to retain ‘a strong sense of connect to culture and identity’ and they thought that the more time that was spent away from home focussing on their education, the more cultural disconnect may occur.…”
Section: Cultural Challengesmentioning
confidence: 99%
“…There is a "heavy, emotional toll" for parents who send their children away to boarding school and are worried about ensuring that "their children retain a strong sense of identity and connection with their culture." [17] Parents: All boarding-school stakeholders must explore how relationships between parents and schools can be strengthened and how effective communication can be fostered by using a range of strategies [9].…”
Section: Addressing the Students And Their Social Needsmentioning
confidence: 99%